1954
DOI: 10.1002/pol.1954.120136908
|View full text |Cite
|
Sign up to set email alerts
|

Second‐order transition temperature of butadiene copolymers

Abstract: Second‐order transition temperature of copolymers of butadiene and the following monomers, acrylonitrile, styrene, dimethylbutadiene, and methyl acrylate has been determined using the dilatometer method. That of polyacrylonitrile has been estimated by extrapolation of data. Mercury or 38% sulfuric acid was used as confining fluids. It has been found that the logarithm of the second‐order temperature in degrees Kelvin is a linear function of the weight fraction of monomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1958
1958
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In contrary, the thermal properties of PAN are not as well characterised [292]. The literature reports a very broad range for the Tg values of PAN from 39 °C to 180 °C [292][293][294][295][296][297][298][299]. Several studies mention two Tg values for PAN homopolymers using DMA and DSC studies, one in the range of ~90-110 °C and another at 140-170 °C [299][300][301][302], while some other studies reported a single Tg [303][304][305][306][307].…”
Section: Thermal Properties Of St-an Copolymersmentioning
confidence: 99%
“…In contrary, the thermal properties of PAN are not as well characterised [292]. The literature reports a very broad range for the Tg values of PAN from 39 °C to 180 °C [292][293][294][295][296][297][298][299]. Several studies mention two Tg values for PAN homopolymers using DMA and DSC studies, one in the range of ~90-110 °C and another at 140-170 °C [299][300][301][302], while some other studies reported a single Tg [303][304][305][306][307].…”
Section: Thermal Properties Of St-an Copolymersmentioning
confidence: 99%